Kemampuan Kapang Dark Septate Endophyte dari Akar Tanaman Aren dalam Menghambat Ganoderma sp. - Dalia Sukmawati; Atin Supiyani Supiyani; Zakiah Nur Afifah; Mutia Balqis Balqis; Nabilah Nov Fikriyyah; Raden Haryo Bimo Setiarto; Dessy Putriana Sari (Jurnal Ilmu Pertanian Indonesia, 2024)
Ganoderma is a fungal pathogen that can cause rot disease at the base of plant stems. This disease threatens oil palm production, especially in Southeast Asia. Trichoderma sp. fungi can control Basal Stem Rot disease in Ganoderma boninense but are ineffective. One solution that can be done to inhibit the growth of Ganoderma sp. is by using Dark Septate Endophyte (DSE) fungi. Research on DSE isolated from sugar palm (Arenga pinnata Merr.) has not been widely studied. The sugar palm plant is related to the oil palm plant in the Arecaceae family. This study aims to analyze the potential of DSE fungi from the roots of the sugar palm plant in inhibiting the pathogenic fungi Ganoderma sp. The stages of this research were isolation and purification of DSE fungi from sugar palm roots, DSE antagonists against Ganoderma sp., and DSE volatile compounds against Ganoderma sp. The results of isolation and purification showed that there were 18 DSE isolates grouped based on morphological similarities in the form of DSE fungi colony colors, where there were ten fungi isolates representing ten different colony colors, namely, isolate A.3.1 (1); A.3.2 (2); A.4.1 (2); A.4.1 (3); A.4.2; A.5.2; A.5.3; A.6.1(a); A.6.2(a); A.6.4(a). A total of 8 fungi isolates were tested for antagonists and volatile compound testing on Ganoderma sp. The results of the antagonist test showed that DSE A4.1(2) had the highest percentage of inhibition with a value of 36.12%, and isolated A6.2 had the highest percentage of inhibition and the lowest with a value of 15.65%. The testing results for volatile compounds showed that the isolate of DSE A4.2 had the highest percentage of inhibition against Ganoderma sp. at 18.25%. In comparison, the lowest inhibition percentage was obtained from DSE A5.2 fungi isolate with a value of 0.43%. Keywords: dark septate endophyte, ganoderma, sugar palm (Arenga pinnata Merr.)